Uji Antimikroba Asap Cair Hasil Pirolisis Sabut Pinang (Areca Catechu L) Terhadap Pertumbuhan Aspergillus flavus dan Rhizopus stoloniferus - Dewi Ayu Novita; Iswendi Iswendi; Iryani Iryani (Jurnal Periodic Jurusan Kimia UNP, 2012)
Aspergillus flavus and Rhizopus stoloniferus are microbes that can cause damage to the food. The existence of these microbes in food can cause illness in humans and animals. One of the efforts made to inhibit the growth of microbes in food is the use of preservatives. Preservatives are being developed right now is the use of organic preservatives that use liquid smoke. Liquid smoke is the smoke of the liquid condensate from the pyrolysis of materials containing cellulose, hemicellulose and lignin such as coco nut. From the pyrolysis of the resulting compounds such as phenol and derivatives, organic acids and carbonyl compounds, which can act as an antimicrobial. This study aims to determine the effect of different concentrations of liquid smoke areca husk pyrolysis results on the growth of microbes that cause food decay, Aspergillus flavus and Rhizopus stoloniferus. This research was conducted at the Laboratory of Chemistry State University of  Padang  with this type of research is experimental. Testing was conducted using paper disc method. Design research is done completely randomized design (RAL) with liquid smoke concentration variation factor. The results showed that the concentration difference factor gives a different effect on the ability of liquid smoke as a result of pyrolysis coco nut antifungal. Highest zone of inhibition at a concentration of 25% (v / v) for Aspergillus flavus is 12 mm, while for Rhizopus stoloniferus is equal to 10 mm.